Tocilizumab (Actemra). Issue 9 (2nd September 2017) - Sheppard, Martin; Laskou, Faidra; Stapleton, Philip P.; Hadavi, Shahryar; Dasgupta, Bhaskar
ABSTRACT: Tocilizumab (TCZ), is a recombinant humanized anti-interleukin-6 receptor (IL-6R) monoclonal antibody which has a main use in the treatment of rheumatoid arthritis, systemic juvenile idiopathic arthritis (sJIA) and polyarticular juvenile idiopathic arthritis (pJIA). This article provides an overview of TCZ including looking into the past at the discovery of interleukin-6 (IL-6) as a pro-inflammatory cytokine. It also looks at how tocilizumab was developed, manufactured and tested to ensure both safety and efficacy in a human population. The article then explores the advantages and disadvantages of using TCZ when compared to other biologics approved in RA, sJIA and pJIA and finally looks ahead to the future and the emerging role of IL-6 and its blockade by TCZ as a treatment for giant cell arteritis (GCA), polymyalgia rheumatica (PMR) and large vessel vasculitis (LVV).